2021
DOI: 10.1007/s00330-020-07455-8
|View full text |Cite
|
Sign up to set email alerts
|

Automated quantitative MRI volumetry reports support diagnostic interpretation in dementia: a multi-rater, clinical accuracy study

Abstract: Objectives We examined whether providing a quantitative report (QReport) of regional brain volumes improves radiologists’ accuracy and confidence in detecting volume loss, and in differentiating Alzheimer’s disease (AD) and frontotemporal dementia (FTD), compared with visual assessment alone. Methods Our forced-choice multi-rater clinical accuracy study used MRI from 16 AD patients, 14 FTD patients, and 15 healthy controls; age range 52–81. Our QReport was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…These patient populations may have more subtle patterns of atrophy and QReports are likely to provide the greatest benefit to raters by flagging patients who require more regular follow-ups and reducing inter-rater variability. The results of diagnostic accuracy studies are ideally published in peer-reviewed journals [19][20][21][116][117][118]. Several companies provide lists of publications on their website.…”
Section: Clinical Validation By End-usersmentioning
confidence: 99%
See 2 more Smart Citations
“…These patient populations may have more subtle patterns of atrophy and QReports are likely to provide the greatest benefit to raters by flagging patients who require more regular follow-ups and reducing inter-rater variability. The results of diagnostic accuracy studies are ideally published in peer-reviewed journals [19][20][21][116][117][118]. Several companies provide lists of publications on their website.…”
Section: Clinical Validation By End-usersmentioning
confidence: 99%
“…Volumetry is widely used in the research setting and has been used to effectively index morphological change from a variety of clinical interventions in phased and randomized controlled trials [9][10][11][12][13][14][15][16][17]. Quantitative volumetric reporting tools (QReports), which automatically quantify an individual patient's regional brain volumes and compare them to healthy, age-specific reference populations, can potentially help neuroradiologists interpret the severity and distribution of brain atrophy and contextualize their findings by referencing normative brain volumes in healthy populations [18][19][20][21][22][23]. The limitations of routine visual assessment reveal the area of clinical need in which such tools can be integrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, recent developments in the field of imaging artificial intelligence (AI) have enabled the automatic extraction of clinically relevant measures from brain MRI scans (Niemantsverdriet et al, 2018;Struyfs et al, 2020;Wittens et al, 2021). Thereupon, it has been shown that automated volumetry, combined with the expertise of radiologists, can improve the sensitivity and specificity of assessing AD-related atrophy (Pemberton et al, 2021). Since combining modern AI technology with radiological expertise has the potential to detect and monitor abnormalities more accurately, a strict validation of AI tools is necessary to assess the validity in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroradiological studies involving raters from different specialities and experience levels have been on the rise in recent years. [2][3][4][5][6][7] Since the advent of MRI, lumbosacral arachnoiditis classification has been based on a three-group system pertaining to the T2-weighted appearance of nerve roots: group 1, the nerve roots clump in the center of the thecal sac; in group 2, the nerve roots adhere to the periphery of the thecal sac; in group 3, the nerve roots form a mass in the thecal sac. However, this paper, the first in the literature to examine radiological classification of lumbosacral arachnoiditis, provides further evidence of heterogeneous imaging findings and encourages moving beyond the traditional three-group classification.…”
mentioning
confidence: 99%